PSIKOEDUKASI PERKEMBANGAN LANSIA KEPADA KADER PUSKESMAS - Sari, Novita (Psikoislamedia: Jurnal Psikologi, 2016)
The number of elderly is getting increase and most of them are experiencing serious psychological disorders. The prevalence of neurotic disorders among elderly in Ngaglik I Sleman-Yogyakarta is quite high and the effective intervention to resolve this issue is much needed. Problems of the elderly should be handled by all parties, both the family and society. Health workers are the closest profession to the elderly as they are easily met by the elderly to get help in the mental health field. Hence, health workers can be trained as the appropriate resources to carry out the programs in order to improve the mental health of the elderly. Therefore, the intervention programs for community cadres is necessary as a health promotion effort for the elderly. Interventions given to the cadres are psychoeducation (related to the elderly development) and relaxation training. The data collected through observation among the elderly and a cadre; the interview among the elderly, cadre of community health center, psychologist, and the village board; the discussion along with cadre of community health center; and written data, such as medical records of elderly patients at the community health center of Ngaglik I. The participants of community interventions are 21 cadres RW 6 Minomartani-Sleman (all female). The results of this study indicated that there is an increased knowledge and insights of participants associated with mental health in the elderly. So through this knowledge, participants are expected to provide counselling and assistance for the elderly who are in their local area.